Evolution of a Gas Embedded Z-pinch: A Quasi Static Zero Dimensional Approach - Soto, Leopoldo (2003)
In gas-embedded Z pinches, high electric discharges are induced in dense gases at atmospheric range pressures. An intriguing phenomenon observed in experiments conducted under these conditions is the radial expansion of the pinch. In this article, a model of Z pinch is derived, which succeeds in explaining expansive Z pinches in terms of variations of the number of particles confined by the pinch. The model is compared with experimental results showing excellent agreement.